Overwintering stages of Callosobruchus chinensis (L.) in the field. Issue 8 (13th August 2020) - Chiluwal, Kashinath; Roh, Gwang Hyun; Park, Chung Gyoo
Abstract: Adzuki bean beetle, Callosobruchus chinensis, is a worldwide oligophagous and a field‐to‐storage pest of legumes including adzuki beans ( Vigna angularis ). Its over‐wintering stage is yet to be confirmed. A series of experiments was carried out at Jinju, in the southern part of the Republic of Korea, to elucidate the overwintering stages. Top‐ and sub‐soil samplings followed by pod and seed samplings from left over plants from adzuki bean fields in the winter of 2015, and an outdoor overwintering test (during Nov 2018 to Jun 2019) by exposing bean seeds harboring different stages (eggs, larvae, pupae, pharates and adults) of laboratory reared C. chinensis to the winter environment were carried out. None of the C. chinensis stages was detected from the top‐ and sub‐soil samples. When the pods and seeds from left over plants were sampled, only a few live pupae were obtained. In the outdoor test with laboratory reared C. chinensis, all the stages (larvae, pupae, and adults), except eggs, were detected on every other weekly samples of infested adzuki bean seeds throughout the winter. These results showed that the overwintering stages of C. chinensis in Jinju, southern Korea, are larvae, pupae, pharates and adults.